Sabina Guzzanti come "star-director" di documentari e docufiction (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The essay illustrates the various strategies that have been put in place by Sabina Guzzanti in her documentaries and docufictions in order to raise herself to the status of a star-director. As such it shows how she has put the documentary and the docufiction at the service of the construction of her star image, and in particular how she has used these two filmic forms in order to avoid giving up those more controversial traits that have characterized her star persona since the late 1990s.